2019
DOI: 10.1002/lt.25381
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Radiofrequency Ablation Efficacy for Hepatocellular Carcinoma by Histology and Pretransplant Radiology

Abstract: Radiofrequency ablation (RFA) represents a potentially curative option for early‐stage hepatocellular carcinoma (HCC). This study aims at evaluating the histologic response after RFA of small HCCs arising in cirrhosis. Data were reviewed from 78 patients with de novo HCCs who were treated with RFA and subsequently transplanted. The last radiological assessment before liver transplantation (LT) was used for comparison between modified Response Evaluation Criteria in Solid Tumors (mRECIST) and histological findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
0
19
2
1
Order By: Relevance
“…However, RFA has recently emerged as a minimally invasive treatment option for hepatic malignancies and as an alternative to resection, especially for patients who have small lesions and/or are unfit for surgical resection [21]. With regard to size, some authors consider RFA a useful technique to provide local control of small, localized, unresectable lesions; in patients with hepatocellular carcinomas (HCCs) 2 cm, for instance, RFA is considered an alternative to hepatic resection because of their comparable long-term efficacy [22,23]. However, the complete ablation rate achieved with RFA declines sharply in the case of larger Univariate and multivariate analysis showed that tumor size less than 20 mm was an independent prognostic factor of LTPFS.…”
Section: Discussionmentioning
confidence: 99%
“…However, RFA has recently emerged as a minimally invasive treatment option for hepatic malignancies and as an alternative to resection, especially for patients who have small lesions and/or are unfit for surgical resection [21]. With regard to size, some authors consider RFA a useful technique to provide local control of small, localized, unresectable lesions; in patients with hepatocellular carcinomas (HCCs) 2 cm, for instance, RFA is considered an alternative to hepatic resection because of their comparable long-term efficacy [22,23]. However, the complete ablation rate achieved with RFA declines sharply in the case of larger Univariate and multivariate analysis showed that tumor size less than 20 mm was an independent prognostic factor of LTPFS.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the characterization models of IS-54 were derived based on ex vivo porcine livers and the proposed correlation might change if there is a large blood vessel in close proximity to the target. Heat sinks caused by large blood vessels during treatment would lead to incomplete thermal coagulation [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study performed in 78 patients with de novo HCCs treated with RFA and subsequently transplanted reported complete pathological response rates of 76.9% in lesions smaller than < 2 cm, 55.0% in lesions 2 to 3 cm, and only 30.8% in lesions above 3 cm. 5 Moreover, high risk of early recurrence after complete ablation has been reported in larger lesions, 6,7 at least partly due to the higher incidence of microsatellite nodules and microvascular invasion. 8,9 Lesion location also plays a major role in treatment success, with perivascular and subcapsular lesions showing lower rates of complete ablation.…”
Section: Combination Therapies: Rationalementioning
confidence: 99%
“…Serra et al reported a complete pathological response rate of 50% in tumors close to the hepatic vessels, compared with 69.3% for tumors distant from the vessels (p ¼ 0.039). 5 Indeed, lesions close to large vessels (< 3 mm) suffer from the so-called "heat sink effect," represented by the heat loss promoted by the adjacent blood flow.…”
Section: Combination Therapies: Rationalementioning
confidence: 99%
See 1 more Smart Citation